Utilization of Ceramics Sanitaryware Waste (CSW) as an Admixture Material of Cooling Paint Products to Apply in Eco-Friendly Sustainability Infrastructure - Kustiawan, Hendra; Boontanon, Suwanna; Aroonsrimorakot, Sayam; Boontanon, Narin (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Sanitaryware is a specific type of ceramic product that holds significant importance in the worldwide ceramics industry. On a global scale, the sanitaryware industry's annual production capacity gradually increased from 352.76 to 391.75 million PCs per year in 2019 to 2021. However, around 28.22 to 30.55 million PCs of these become rejected products, wherein it has including non-biodegradable waste. This study aims to examine the potential of ceramics sanitaryware waste as an admixture material in cooling paint products to mitigate the global warming impact and promote environmental sustainability. The techniques employed involve the combination of ceramics sanitaryware waste in diverse compositions embedded into the acrylic paint, subsequent applications were coated into substrates. Furthermore, measurements were carried out encompassing chemical, physical, and performance analysis. The findings of X-ray fluorescence analysis indicate that ceramics sanitaryware waste is predominantly composed of SiO2 and Al2O3 over 90% with Mullite and Quartz as the major compounds in X-ray diffraction. The density and acidity resulted in 1.1 g/cm3 and 7. The solar reflectance achieved an average thermal performance of 91.12%, while the thermal emittance achieved a thermal performance of 98.50%. Heat resistance has resulted in a maximum reduce temperature of -8.5⁰C indoors and -10.5⁰C outdoors. The thermal images have shown that ceramic sanitaryware waste can reflect sunlight average of 9⁰C compared with ambient. Moreover, in terms of efficiency, cooling paint made from ceramics sanitaryware waste could be estimated to yield energy savings between 25.5% to 31.5% and reduce CO2 emissions around 0.0384 KgCO2eq /0C. The study revealed that it can be demonstrated that Ceramics Sanitaryware Waste has significant potential as admixture materials in cooling paint as an alternative solution to combat the heat phenomenon in urban areas and lessen the impact of climate change and global warming.